EDITORIAL: ITALIAN THEATRE IN THE 21st CENTURY - Daraklitsa, Elina (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The present introductory study in the special issue dedicated to 21st-century Italian theatre, published in the 20th issue of Parabasis, the journal of the Department of Theatre Studies of the National and Kapodistrian University of Athens, focuses on the themes addressed by the authors of the ten studies included in the tribute. Building upon existing scholarly material, the study delves into the social, political, and environmental dimensions of contemporary Italian theatre, which engages in an active dialogue with digital technology and hybrid forms of performance. The aesthetics of Romeo Castellucci, Giorgio Strehler, and Lluís Pasqual, the eco-dramaturgy, the new dramaturgical and performative expressions that emerged through the post-pandemic theatrical experience, as well as the postmodern reception of Luigi Pirandello’s works in the digital sphere, collectively constitute the rich spectrum of the author’s in-depth research approaches, which enrich the ongoing scholarly dialogue in the field of contemporary theatre studies.